In-game-advertising (advergame) as an alternative tools in increasing local brand awareness / Suzani Azmin - Azmin, Suzani (2006)
Advergaming had proven to be successful in United States market with million of people visiting online gaming sites. In India, mobile gaming would be a more popular platform for advergames, than the Internet. Meanwhile in Malaysia, the market of advergaming is still at its infant stage. This study is to identify the potential of advergaming to enter the local branding market in Malaysia. Numerous people had to be interviewed and they are related to gaming industry. A survey was conducted to the Internet users especially among students. The following findings indicate that the potential of advergaming for local brandings can be available in two to five years time in Malaysia. The current Digital Technology is available to support gaming and advertising industry in Malaysia, however there is no market yet for advergaming. The success of advagaming in Malaysia can be made possible with further research, in the future.